2019
DOI: 10.1097/nmd.0000000000001012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Impulsivity and Clinical and Sociodemographic Variables Among Lebanese Patients With Bipolar Disorder

Abstract: Impulsivity is a psychiatric symptom that seems to be more prevalent in some mental disorders such as bipolar disorders (BDs). It is a trait that seems to be influenced by many clinical and sociodemographic variables across BD. To examine the relationship between impulsivity and these variables, we performed a cross-sectional study on 50 patients diagnosed with BD and 50 healthy subjects. Both groups were administered the Barratt Impulsiveness Scale; the Structural Clinical Interview for Diagnostic and Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…Violence was also shown to be associated with the presence of BD according to our results, in line with a previous Lebanese study 36 . Indeed, previous findings showed that a person who has been suffering from violence in the family, can develop many unwanted physical, mental, and psychological problems as a result of these actions and behaviors 49 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Violence was also shown to be associated with the presence of BD according to our results, in line with a previous Lebanese study 36 . Indeed, previous findings showed that a person who has been suffering from violence in the family, can develop many unwanted physical, mental, and psychological problems as a result of these actions and behaviors 49 …”
Section: Discussionsupporting
confidence: 92%
“…This study evaluates the association of eating attitudes with bipolar disorder in Lebanese patients after adjustment over some factors that have previously been shown to be associated with BD. 36 The major finding was that having eating disorders (measured by the EAT) was significantly associated with the presence of bipolar disorder. In fact, eating disorders are an independent factor associated with BD, not mediated by other factors included in the multivariable analyses (marital status, family history of violence, shopping and gambling addictions, sleep quality, and insomnia severity).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…BPD patients in a manic state represent the characteristic behaviors such as hyperactivity, impulsivity, and aggressiveness [ 28 , 29 ]. Rodent models of mania have also shown the hyperactive- and the impulsive-like behaviors, increasing the total number of entries into the arms and the frequencies of the open arm entries/the spent time in the open arms in the EPM test [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%